Synthesis and characterization of bio-based flame-retardant coating for cotton fabric - Nurul Hidayah, Abu Bakar; Wan Norfazilah, Wan Ismail (Elsevier Ltd, 2025)
The study explored the use of plant-derived bio-based materials for creating flame-retardant coatings on cotton fabric. Two formulations were prepared: one using banana peel powder combined with ammonium phosphate (BPE/(NH4)3PO4), and the other using soybean and ammonium phosphate with pumpkin extract (soybean/(NH4)3PO4−pumpkin extract). The Gas-Chromatography-Mass Spectrometry (GC-MS) analysis confirmed the presence of flame-retardant organic compounds in both formulations. The Scanning Electron Microscope (SEM) imaging revealed a uniform and smooth coating on the fabric treated with soybean/(NH4)3PO4−pumpkin extract, whereas the fabric coated with BPE/(NH4)3PO4 exhibited uneven deposition and small agglomerates. Both vertical burning test and Thermogravimetric analysis (TGA) were conducted to assess the fabric’s flame resistance and thermal properties. The vertical burning test demonstrated that the coated cotton fabric sustained minimal damage, ignited later, and had shorter char length compared to the uncoated fabric. Increasing the bio-based materials in both coatings contributed to this effect. TGA analysis revealed that the coated cotton fabric retained more mass at elevated temperatures than the uncoated fabric. Both burning tests confirmed the efficacy of the bio-based flame-retardant coating on cotton fabric, validating the success of this study.